Electronic technical assistance services quality: mediation role of brand image and satisfaction on repurchase intention - Vieira, Renan Araújo; Aguiar, Edvan Cruz; Costa, Marconi Freitas da; Policarpo, Manoela Costa (Revista de Administração da UFSM, 2022)
Purpose – This study analyzed the relationship between the perceived quality of electronic equipment technical assistance services with the intention of repurchasing, with the serial mediation model of satisfaction and brand image. Design/methodology/approach – A quantitative research of a described character was carried out and the survey method was adopted with technical assistance clients (n = 158). The conceptual model was evaluated using regression with bootstrapping. And, for the analysis of the mediation effects, with two mediating variables, an adaptation of the macro PROCESS (Hayes, 2017) was made for the software R. Therefore, four hypotheses were assessed by a cross-section research method using mediation analysis. Findings – The results indicate that general customer satisfaction mediates the relationship between the quality of the service perceived and the intentions to repurchase. In this sense, it can be concluded that the relationships between the perceived quality in services and the intentions of repurchase only occur through mediation for satisfaction or through the hierarchical causal relationship between satisfaction and image. The empirical test of the proposed model through a serial mediation approach expands the possibilities on understanding consumer brand affiliation processes. Moreover, it highlights the importance of assistance service companies as brand partners. Originality/value – The main contribution of this research is that satisfaction and brand image are positively associated with the intention to repurchase as reflections of the perceived quality by the technical assistance services of electronic products. Thus, the work shows that customers perceive the quality of the service, and this, in turn, provides positive consequences for both the service provider and the manufacturer (repurchase intentions) and for the customer (satisfaction). Design/methodology/approach – The survey was adopted with an instrument adapted from Yang (2010) and Christino et al. (2019) validated by experts. Made available online, the instrument collected 309 responses for analysis using the structural equation modeling technique. Findings – The results validated the positive relationships for Facilitating Conditions, Hedonic Motivation, Perceived Value, Habit and Performance Expectation - the highest’s coefficients. The influence of Expectation on Effort and Social Influence has not been validated. Research limitations/implications – The results cannot be generalized to all Brazilian individuals, in addition to considering recognized determinants of international literature. For this reason, suggestions are made for continuing and deepening the research. Practical implications – The results contribute by indicating the main perceptions that lead to the intention and use of discount coupons, which are the performance expectation and the habit. Thus, managers can develop their sales strategies considering such factors while society can establish strategies to more sustainable purchases. Originality/value – The research discusses the determinants of UTAUT2 in the Brazilian context to explain the intention and behavior of using online discount coupons, which are grouped together are unprecedented in Brazilian literature.